2017
DOI: 10.1177/0957650917722454
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations of tip clearance flow and loss in a variable geometry turbine cascade

Abstract: Variable geometry turbines are widely employed to improve the off-design performance of gas turbine engines; however, there is a performance penalty associated with the vane-end partial gap required for the movement of variable vanes. This paper is a continuation of the previous work and aims to understand the leakage flow and loss mechanisms under the influence of the pivoting axis. Experimental investigations with a variable geometry turbine linear cascade have been conducted for tip gap heights of 1.1% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
10
0
3
Order By: Relevance
“…涡轮变几何后, 必须在静叶端部留有间隙并设置 旋转轴 [25] (图4), 以保证静叶的自由转动, 这样就会引 起静叶端区的附加损失, 导致涡轮效率的下降, 同时 也增加了控制系统的复杂性 [13,19] .…”
Section: 可调静叶端区流场特性unclassified
See 2 more Smart Citations
“…涡轮变几何后, 必须在静叶端部留有间隙并设置 旋转轴 [25] (图4), 以保证静叶的自由转动, 这样就会引 起静叶端区的附加损失, 导致涡轮效率的下降, 同时 也增加了控制系统的复杂性 [13,19] .…”
Section: 可调静叶端区流场特性unclassified
“…哈尔滨工程大学刘顺隆等人 [26] 图 3 变几何动力涡轮与定几何动力涡轮的性能对比 [21] 图 4 (网络版彩图)可调静叶旋转轴结构 [25] 值得注意的是, 现代船舶燃气轮机动力涡轮大多 在对可调静叶级匹配影响方面, 冯永明等人 [7,22,34] 通过忽略可调静叶端部间隙的影响, 初步数值研究了 由于涡轮级间相互干扰, 可调静叶级的通流特性 变化将显著影响整个变几何涡轮的气动特性 [37] . 高杰 等人 见国外相关公开报道.…”
Section: 可调静叶端区流场特性unclassified
See 1 more Smart Citation
“…The results of some pieces of literature showed that the performance of compressor and cascade could be improved as the separation flow was controlled by introducing an appropriate clearance size. While a larger clearance size led to the enhancement of the TLF, which would decrease the performance of the compressor (Zuo et al 2011;Chen et al 2012Chen et al , 2013Gottschall et al 2012;Gao et al 2017). In addition, Liu et al (2016a) and Mao et al (2019) explored the effect of tip clearance of the rotors on the performance of a counter-rotating axial flow compressor.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Some combined control technologies at the clearance region have been put forward recently, e.g. casing treatment and blowing, 8 winglet and squealer, 9,10 and honeycomb seal. 11,12 However, the relative motion between the blade and shroud endwall has been neglected in these studies.…”
Section: Introductionmentioning
confidence: 99%